Preparation method of CuPt-CSTO nano composite material
The CuPt-CSTO nanocomposite material addresses STO's limited visible light response by incorporating Cu-Pt bimetallic elements, enhancing electron-hole separation and redox activity for efficient hydrogen production.
Patent Information
- Application Number
- CN202411627470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Strontium Titanate (STO) has a large bandgap width (3.2eV) and lacks response to visible light, limiting its photocatalytic water decomposition quantum efficiency.
A two-step photodeposition method is used to create a CuPt-CSTO nanocomposite material by loading Cu-Pt bimetallic elements onto Cr-doped SrTiO3, enhancing visible light response and improving electron-hole separation and redox activity.
The CuPt-CSTO nanocomposite material exhibits strong visible light response, tight interface bonding, rich redox active sites, and high reduction potential, leading to improved hydrogen production efficiency.
Smart Images

Figure CN119140119A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar energy and photocatalytic hydrogen production, and in particular to a method for preparing a CuPt-CSTO nanocomposite material. Background Art
[0002] Strontium Titanate SrTiO 3 (hereinafter referred to as STO) is a perovskite oxide with the characteristics of an n-type semiconductor, a wide bandgap and excellent electronic properties. Because its band structure is suitable for the water redox potential level and is conducive to the formation of hydrogen and oxygen, it has been widely studied and used for photocatalytic water decomposition. However, STO has a large bandgap width (3.2eV) and has almost no response to visible light, which limits its photocatalytic water decomposition quantum efficiency. Summary of the invention
[0003] To this end, the present invention provides a method for preparing a CuPt-CSTO nanocomposite material, and prepares a CuPt-CSTO nanocomposite material hydrogen production photocatalyst by a two-step photodeposition method.
[0004] The present invention adopts the following technical solution:
[0005] A method for preparing a CuPt-CSTO nanocomposite material comprises the following steps:
[0006] (1) Take a certain amount of Sr(NO 3 ) 2 Dissolve in an appropriate amount of deionized water and stir for 10-120 minutes;
[0007] (2) Take a certain amount of KOH powder and dissolve it in an appropriate amount of deionized water. After the solution cools down, slowly add a certain amount of TiO 2 , stirring for 10-120 minutes;
[0008] (3) Mix the solutions obtained in step (1) and step (2), stir vigorously for 20-120 min, and then add a certain amount of Cr(NO 3 ) 3 , continue stirring for 0.5-12h;
[0009] (4) The stirred solution is transferred into a hydrothermal reactor, kept at a certain temperature for 6-48 hours, cooled naturally to room temperature, washed with deionized water until the product is neutral, and vacuum dried at a certain temperature for 6-36 hours to obtain CSTO. CSTO reduces the band gap of STO and extends its visible light response absorption edge to 500-600nm;
[0010] (5) Take a certain amount of CSTO and disperse it in an appropriate amount of methanol aqueous solution with a volume concentration of 60%, add a certain amount of CuCl 2After bubbling with high-purity nitrogen for 5-120 minutes to remove dissolved oxygen, the suspension was stirred for 5-120 minutes and irradiated with visible light from a 300W xenon lamp for 0.5-24 hours to achieve in-situ photodeposition of Cu metal precursor loading;
[0011] (6) collecting the product obtained in step (5), washing it with deionized water and ethanol for several times, and vacuum drying it at a certain temperature for 6-36 hours to obtain a hydrogen production photocatalyst of Cu metal photodeposited on CSTO, namely Cu-CSTO, and obtaining in situ photodeposited Cu metal modified CSTO;
[0012] (7) Take a certain amount of Cu-CSTO obtained in step (6) and disperse it in an appropriate amount of methanol aqueous solution with a volume concentration of 60%, and add a certain amount of H 2 PtCl 6 6H 2 O, bubbling with high-purity nitrogen for 5-120 min to remove dissolved oxygen, stirring the suspension for 5-120 min, and irradiating with visible light from a 300W xenon lamp for 0.5-24 h, achieving in-situ photodeposition of CuPt bimetallic precursor loading;
[0013] (8) Collect the product obtained in step (7), wash it with deionized water and ethanol several times, and vacuum dry it at a certain temperature for 6-36 hours to obtain a CuPt-CSTO nanocomposite hydrogen production photocatalyst. The obtained in situ photodeposited CuPt bimetallic modified CSTO significantly improves the separation and migration ability of the photogenerated electrons and holes and the activity of decomposing water to produce hydrogen.
[0014] Preferably, the Sr(NO 3 ) 2 The mass of is 0.1-10g, and the volume of deionized water is 5-500mL.
[0015] Preferably, the mass of KOH used in step (2) is 0.01-5 g, the volume of deionized water is 5-500 mL, and the TiO 2 The mass is 0.1-5g.
[0016] Preferably, the Cr(NO 3 ) 3 The mass is 0.01-1g.
[0017] Preferably, the temperature of the hydrothermal reactor in step (4) is 120-360°C; and the vacuum drying temperature is 50-90°C.
[0018] Preferably, the mass of CSTO used in step (5) is 0.01-5 g, the volume of methanol aqueous solution is 10-500 mL, and the CuCl 2 The mass is 0.01-5g.
[0019] Preferably, the vacuum drying temperature in step (6) is 50-100°C.
[0020] Preferably, the mass of Cu-CSTO used in step (7) is 0.01-5 g, the volume of methanol aqueous solution is 10-500 mL, and H 2 PtCl 6 6H 2 The mass of O is 1-500 mg.
[0021] Preferably, the vacuum drying temperature in step (8) is 50-100°C.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] The embodiment of the present application provides a method for preparing a CuPt-CSTO nanocomposite material. The Cu-Pt bimetal and CSTO are compounded by a two-step photodeposition method to construct a CuPt-CSTO nanocomposite material, which significantly improves the response and absorption capacity of CSTO to visible light, and successfully improves the separation and migration capacity of photogenerated electrons and holes. The obtained CuPt-CSTO nanocomposite material has the advantages of strong visible light response ability, tight interface bonding, stable structure, rich redox active sites, high reduction potential and hydrogen production activity, and can be applied to solar energy and photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD (X-ray diffraction) pattern of the sample prepared in Example 2.
[0025] Figure 2 These are TEM (transmission electron microscope) images and lattice fringes of the CuPt-CSTO composite material prepared in Example 2 at different magnifications.
[0026] Figure 3 The graphs show the photocatalytic hydrogen production amount and hydrogen production rate of different samples, as well as the hydrogen production cycle stability test graph of Cu10Pt5-5CSTO. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0028] In the related art, the doping valence is lower than Ti 4+ Cations such as Mg 2+ Cr 3+ and Al 3+ , which can avoid Ti3+ The introduction of defects, and Ti 3+ Defects are recombination centers for photogenerated charges, and doping with external elements can also introduce intermediate states within the band gap of STO, thereby enhancing its visible light absorption. The ion radius of Cr is larger than that of Ti but smaller than that of Sr, and the occupied Cr energy level is usually 2.2 eV lower than the bottom of the conduction band formed by the Ti 3d orbital or 1.0 eV higher than the top of the valence band formed by the O 2p orbital, which means that Cr doping can narrow the band gap of STO and achieve visible light response. However, the hydrogen production effect of single-element doped photocatalysts is always restricted by factors such as high degree of recombination of photogenerated carriers and lack of active sites for redox reactions.
[0029] In view of this, the design idea of the embodiment of the present application is: the loading of Cu-Pt bimetallic elements, due to the synergistic catalytic effect between the two, can not only promote the separation of electrons and holes in the matrix material and improve the carrier transmission capacity, but also provide the matrix material with abundant redox reaction active sites, thereby improving the hydrogen evolution activity of the material. Therefore, in order to solve the problems of easy recombination of photogenerated electrons and holes and lack of active sites in the single-element doped photocatalytic material CSTO, the Cu-Pt bimetal is introduced by the in-situ photodeposition method, and the CSTO with a high degree of photogenerated carrier recombination and fewer redox reaction active sites is compounded with the Cu-Pt bimetal, thereby improving the carrier separation efficiency and redox activity. This is an effective strategy to improve the photocatalytic efficiency.
[0030] Specifically, the present invention provides a method for preparing a CuPt-CSTO nanocomposite material, which uses a two-step photodeposition method to composite Cu-Pt bimetallic and CSTO to achieve Cu-Pt bimetallic and Cr-doped SrTiO 3 The interface co-assembly of CuPt and CSTO gives a CuPt-CSTO nanocomposite hydrogen production photocatalyst with tight interface bonding, strong visible light response ability, rich redox active sites, good stability and high reduction potential.
[0031] In order to illustrate the technical solution described in this application, a specific embodiment is provided below for illustration. Example 1
[0032] A method for preparing a CuPt-CSTO nanocomposite material.
[0033] (1) Take 2.12 g of Sr(NO 3 ) 2 As raw material, dissolve in 80mL deionized water; take 0.2g KOH and dissolve in 80mL deionized water, after cooling, slowly add 0.8g TiO 2 , and stirred for 100 min.3 ) 2 Solution and TiO 2 The suspension was stirred vigorously for 100 min, and then 0.13 g Cr(NO 3 ) 3 After continuous stirring for 10 h, the mixture was transferred into a hydrothermal reactor and kept at 200 °C for 10 h. The obtained product was washed with water until neutral and then vacuum dried at 60 °C for 15 h to obtain SrTiO doped with 5% Cr by molar ratio. 3 (5CSTO);
[0034] (2) Disperse 200 mg of 5CSTO in 200 mL of 60% methanol aqueous solution, and add 10 mg of CuCl 2 , after bubbling with high-purity nitrogen for 20 min to remove dissolved oxygen, stirring was continued for 20 min, and visible light irradiation with a 300 W xenon lamp was performed for 6 h. The obtained product was washed with deionized water and ethanol several times and then vacuum dried at 70 °C for 10 h to obtain 5 wt.% Cu-loaded 5CSTO (Cu5-5CSTO);
[0035] (3) Take 200 mg of Cu5-5CSTO and disperse it in 200 mL of 60% methanol aqueous solution, then add 1.0 mg H 2 PtCl 6 6H 2 O, bubbling with high-purity nitrogen for 30 min to remove dissolved oxygen, and then stirring for 40 min. The product was irradiated with visible light from a 300 W xenon lamp for 10 h. The product was washed with deionized water and ethanol several times and dried in vacuum at 70 °C for 10 h to obtain 0.5 wt.% Pt-loaded Cu5-5CSTO (Cu5Pt5-5CSTO). Example 2
[0036] A method for preparing a CuPt-CSTO nanocomposite material.
[0037] (1) Take 1.06 g of Sr(NO 3 ) 2 As raw material, dissolve in 40mL deionized water; take 0.1g KOH and dissolve in 40mL deionized water, after cooling, slowly add 0.4g TiO 2 , and stirred for 60 min. 3 ) 2 Solution and TiO 2 The suspension was stirred vigorously for 60 min, and then 0.065 g Cr(NO 3 ) 3After continuous stirring for 6 hours, the mixture was transferred into a hydrothermal reactor and kept at 180°C for 12 hours. The obtained product was washed with water until neutral and then vacuum dried at 80°C for 12 hours to obtain Cr-doped SrTiO with a molar ratio of 5%. 3 (5CSTO);
[0038] (2) Disperse 100 mg of 5CSTO in 100 mL of 60% methanol aqueous solution, and then add 10 mg of CuCl 2 , after bubbling with high-purity nitrogen for 30 min to remove dissolved oxygen, stirring was continued for 30 min, and visible light irradiation with a 300 W xenon lamp was performed for 8 h. The obtained product was washed with deionized water and ethanol several times and then vacuum dried at 80 °C for 12 h to obtain 10 wt.% Cu-loaded 5CSTO (Cu10-5CSTO);
[0039] (3) Take 100 mg of Cu10-5CSTO and disperse it in 100 mL of 60% methanol aqueous solution, then add 0.5 mg H 2 PtCl 6 6H 2 O, bubbling with high-purity nitrogen for 30 min to remove dissolved oxygen, and then stirring for 30 min. The product was irradiated with visible light from a 300 W xenon lamp for 8 h. The product was washed with deionized water and ethanol several times and then dried in vacuum at 80 °C for 12 h to obtain 0.5 wt.% Pt-loaded Cu10-5CSTO (Cu10Pt5-5CSTO).
[0040] As an example, Figure 1 : is the XRD diagram of the sample prepared in Example 2. The horizontal axis represents the 2θ angle, and the vertical axis represents the intensity (au).
[0041] As an example, Figure 2 These are TEM images and lattice fringes of the CuPt-CSTO composite material prepared in Example 2 at different magnifications.
[0042] For example, Figure 2 Regions (a), (b), (c) and (d) in the figure respectively represent TEM images and lattice fringes with scales of 100nm, 10nm, 10nm and 50nm. Partially enlarged images of lattice fringes are also shown in the upper right corner and lower right corner of regions (b) and (c).
[0043] For example, in area (b), SrTiO 3 The interplanar spacing d of the 110 crystal plane of Cu is 0.27 nm, the interplanar spacing d of the 111 crystal plane of Cu is 0.2 nm, and the interplanar spacing d of the 111 crystal plane of Pt is 0.22 nm. For example, in region (c), SrTiO3 The interplanar spacing d of the 110 crystal plane of Cu is 0.27 nm, the interplanar spacing d of the 111 crystal plane of Cu is 0.2 nm, and the interplanar spacing d of the 111 crystal plane of Pt is 0.22 nm. Example 3
[0044] A method for preparing a CuPt-CSTO nanocomposite material.
[0045] (1) Take 3.18 g of Sr(NO 3 ) 2 As raw material, dissolve in 120mL deionized water; take 0.3g KOH and dissolve in 120mL deionized water, after cooling, slowly add 1.2g TiO 2 , and stirred for 120 min. 3 ) 2 Solution and TiO 2 The suspension was stirred vigorously for 120 min, and then 0.195 g Cr(NO 3 ) 3 After continuous stirring for 12 hours, the mixture was transferred into a hydrothermal reactor and kept at 240°C for 14 hours. The obtained product was washed with water until neutral and then vacuum dried at 60°C for 24 hours to obtain Cr-doped SrTiO with a molar ratio of 5%. 3 (5CSTO);
[0046] (2) Take 300 mg of 5CSTO and disperse it in 300 mL of 60% methanol aqueous solution, then add 45 mg of CuCl 2 , after bubbling with high-purity nitrogen for 90 min to remove dissolved oxygen, stirring was continued for 90 min, and visible light irradiation with a 300 W xenon lamp was performed for 12 h. The obtained product was washed with deionized water and ethanol several times and then vacuum dried at 60 °C for 24 h to obtain 15 wt.% Cu-loaded 5CSTO (Cu15-5CSTO);
[0047] (3) Take 300 mg of Cu15-5CSTO and disperse it in 300 mL of 60% methanol aqueous solution, then add 1.5 mg of H 2 PtCl 6 6H 2 O, bubbling with high-purity nitrogen for 90 min to remove dissolved oxygen, and then stirring for 90 min. The product was irradiated with visible light from a 300 W xenon lamp for 12 h. The product was washed with deionized water and ethanol several times and then dried in vacuum at 60 °C for 24 h to obtain 0.5 wt.% Pt-loaded Cu15-5CSTO (Cu15Pt5-5CSTO). Example 4
[0048] The photocatalytic performance test was carried out, and the photocatalytic overall water decomposition reaction was carried out on a photocatalytic hydrogen production system equipped with a gas circulation system. In detail, 50 mg of the sample (i.e., CuPt-CSTO nanocomposite) was added to 100 mL of a 10 vol.% methanol aqueous solution, ultrasonically dispersed for 30 min, and then transferred to a top radiation photoreactor. A 280 W xenon lamp was used as the light source. Before the measurement, the gas circulation system was evacuated to remove the air. During the test, the temperature of the cooling water circulation system was maintained at 5 ° C. The amount of hydrogen produced was detected by equipping a thermal conductivity detector and a gas chromatograph. The experiment was carried out for 3 h each time, and the amount of hydrogen was measured every 0.5 h, and then the hydrogen production cycle stability test was carried out.
[0049] As an example, Figure 3 The graphs show the photocatalytic hydrogen production amount and hydrogen production rate of different samples, as well as the hydrogen production cycle stability test graph of Cu10Pt5-5CSTO.
[0050] For example, Figure 3 The (a) area is the photocatalytic hydrogen production of different samples, and the vertical axis unit is μmol·g -1 , represents the amount of micromoles of hydrogen produced per gram of sample, and the abscissa represents time (h).
[0051] For example, area (b) is the hydrogen production rate diagram of different samples, and the vertical axis unit is μmol·h -1 ·g -1 , represents the rate of micromoles of hydrogen produced per gram of sample per hour, and the horizontal axis represents different samples.
[0052] For example, the (c) and (d) regions constitute the hydrogen production cycle stability test diagram of Cu10Pt5-5CSTO. The vertical axis of the (c) region is in μmol, which represents the amount of micromolar hydrogen produced in the photocatalytic reaction, and the horizontal axis represents time (h). The vertical axis of the (d) region is in μmol·h -1 ·g -1 , which represents the rate of micromoles of hydrogen produced per gram of sample per hour.
[0053] Therefore, from Figure 3 It can be seen from the test results that the CuPt-CSTO nanocomposite material provided in the embodiments of the present application has a good photocatalytic hydrogen production effect, a high hydrogen production amount and a high hydrogen production rate per gram of sample, and a relatively stable hydrogen production rate.
[0054] Without limitation to this, any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A method for preparing a CuPt-CSTO nanocomposite material, characterized in that: The following steps are involved: (1) Take a certain amount of Sr(NO3)2 and dissolve it in an appropriate amount of deionized water, and stir for 10-120 minutes; (2) Take a certain amount of KOH powder and dissolve it in an appropriate amount of deionized water. After the solution cools down, slowly add a certain amount of TiO2 and stir for 10-120 minutes; (3) Mix the solutions obtained in step (1) and step (2), stir vigorously for 20-120 min, add a certain amount of Cr(NO3)3, and continue stirring for 0.5-12 h; (4) The stirred solution is transferred into a hydrothermal reactor, kept at a certain temperature for 6-48 hours, cooled naturally to room temperature, washed with deionized water until the product is neutral, and vacuum dried at a certain temperature for 6-36 hours to obtain CSTO; (5) Take a certain amount of CSTO and disperse it in an appropriate amount of methanol aqueous solution with a volume concentration of 60%, add a certain amount of CuCl2, bubble it with high-purity nitrogen for 5-120 minutes to remove dissolved oxygen, continue to stir the suspension for 5-120 minutes, and irradiate it with visible light from a 300W xenon lamp for 0.5-24 hours; (6) collecting the product obtained in step (5), washing it with deionized water and ethanol for several times, and vacuum drying it at a certain temperature for 6-36 hours to obtain a hydrogen production photocatalyst of Cu metal photodeposited on CSTO, i.e., Cu-CSTO; (7) taking a certain amount of Cu-CSTO obtained in step (6) and dispersing it in an appropriate amount of methanol aqueous solution with a volume concentration of 60%, adding a certain amount of H2PtCl6·6H2O, bubbling with high-purity nitrogen for 5-120 minutes to remove dissolved oxygen, stirring the suspension for 5-120 minutes, and irradiating it with visible light from a 300W xenon lamp for 0.5-24 hours; (8) Collect the product obtained in step (7), wash it with deionized water and ethanol for several times, and vacuum dry it at a certain temperature for 6-36 hours to obtain a CuPt-CSTO nanocomposite material.
2. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The mass of Sr(NO3)2 used in step (1) is 0.1-10 g, and the volume of deionized water is 5-500 mL.
3. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The mass of KOH used in step (2) is 0.01-5 g, the volume of deionized water is 5-500 mL, and the mass of TiO2 is 0.1-5 g.
4. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The mass of Cr(NO3)3 used in step (3) is 0.01-1g.
5. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: In step (4), the temperature of the hydrothermal reactor is 120-360°C; and the vacuum drying temperature is 50-90°C.
6. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The mass of CSTO used in step (5) is 0.01-5 g, the volume of methanol aqueous solution is 10-500 mL, and the mass of CuCl2 is 0.01-5 g.
7. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The vacuum drying temperature in step (6) is 50-100°C.
8. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The mass of Cu-CSTO used in step (7) is 0.01-5 g, the volume of methanol aqueous solution is 10-500 mL, and the mass of H2PtCl6·6H2O is 1-500 mg.
9. The method for preparing a CuPt-CSTO nanocomposite material according to claim 1, characterized in that: The vacuum drying temperature in step (8) is 50-100°C.
Citation Information
Patent Citations
Method for one-step microwave synthesis of La-Cr co-doped strontium titanate
CN104399452A
Method for preparing oxygen-vacancy-containing strontium titanate photocatalyst
CN107552033A
Preparation method of silver phosphate composite photocatalyst for treating malachite green in water
CN107824207A
Silver phosphate composite photocatalyst for treating rose bengal B in high-salt wastewater and preparation method and application of photocatalyst
CN110201722A
Strontium titanate photocatalyst capable of completely decomposing water by visible light as well as preparation method and application of strontium titanate photocatalyst
CN117427667A
Cited By
Ni-MoOx / HTO nano-catalyst as well as preparation method and application thereof
CN120381846A
Ni-MoO x / HTO nanocatalyst and its preparation method and application
CN120381846B
